PLL-BASED 3? INVERTER CIRCUIT FOR MICROGRID SYSTEM OPERATED BY ELECTROSTATIC GENERATOR - Motakabber, S.M.A; Rahman, Tawfikur; Ibrahimy, Muhammad I.; Alam, A. H. M. Zahirul (IIUM Engineering Journal, 2019)
A current source control based PLL (phase lock loop) technique is one of the most efficient methods for modern 3? synchronized grid power systems. When an inverter circuit is driven by an electrostatic generator with wind power, it encounters some problems, such as static and dynamic turn-on-off switching losses, unbalanced source voltage, low continuous current, higher frequency harmonic distortion, phase angle imbalance, etc. To solve these problems, a series of connected switching inverter modules technique is proposed. It is not only a traditional inverter system, but it also works as a low-frequency ripple current inverter with lower switch losses. A new topology of phase synchronous inverter (PSI) is designed using a PLL current source controller. The input voltage source of the PSI is a high DC voltage from an electrostatic generator (ESG). The modified ESG is capable of generating the HVDC and a continuous moderate amount of current. The proposed switching topology of the inverter is able to control the microgrid power as well as reduce the dynamic and static switching loss. It also reduces the high-frequency harmonic distortion and improves the phase angle error. The output LCL lowpass filter scheme of the inverter is designed to reduce the total harmonic distortion of 1.62%. The PSI circuit is designed and simulated using MATLAB software. In the developed system, the input voltage of 8 k , microgrid frequency of 50Hz, switching frequency of the carrier of 10 kHz, and modulation index of 0.85 are considered to be implemented. The proposed novel microgrid connected PSI switching module design technique has significantly enhanced the power stability. The overall system efficiency improved by 95.52%. ABSTRAK: Sumber-arus terkawal berdasarkan teknik PLL (fasa litar kunci) adalah satu kaedah cekap bagi sistem moden tenaga grid selaras 3?. Apabila litar songsang (inverter) digerak menggunakan penjana elektrostatik bersama tenaga angin, ia mengalami masalah seperti kehilangan tenaga statik dan dinamik suis hidup-mati, sumber voltan yang tidak seimbang, kurang arus terus, gangguan harmoni frekuensi tinggi, ketidak-seimbangan sudut fasa, dan sebagainya. Bagi menyelesaikan masalah ini, teknik modul suis bersiri dihubung bersama inverter telah dicadangkan. Ini bukan semata-mata teknik lama sistem inverter, tetapi ia juga berfungsi sebagai arus tidak tetap frekuensi-rendah dengan kurang kehilangan tenaga pada suis inverter. Topologi baru fasa inverter tetap (PSI) ini telah direka menggunakan kawalan sumber arus PLL. Sumber voltan masuk PSI ini telah digunakan daripada voltan DC tinggi penjana elektrostatik (ESG). ESG yang diubah suai ini dapat menghasilkan HVDC dan arus terus yang sederhana. Topologi suis inverter yang dicadang ini dapat mengawal kuasa mikrogrid serta mengurangkan kehilangan dinamik dan statik suis. Ia juga mengurangkan gangguan harmoni frekuensi tinggi dan memperbaiki ketidak-seimbangan sudut fasa. Skim tapisan signal keluar yang rendah pada LCL inverter ini direka bagi mengurangkan total gangguan harmoni sebanyak 1.62%. Litar PSI ini direka dan disimulasi menggunakan perisian MATLAB. Dalam sistem yang dibangunkan ini, 8 kVDCvoltan masuk, 50Hz frekuensi mikrogrid, 10 kHz frekuensi suis angkutan dan 0.85 indeks modulasi telah dipertimbangkan untuk kegunaan. Teknik baru modul suis PSI mikrogrid bersambung yang dicadangkan ini mempunyai kepentingan dalam menstabilkan kuasa dan memperbaiki kecekapan sistem keseluruhan sebanyak 95.52%.